2019
DOI: 10.1021/acs.jpca.9b02217
|View full text |Cite
|
Sign up to set email alerts
|

Large Intermediates in Hydrazine Decomposition: A Theoretical Study of the N3H5 and N4H6 Potential Energy Surfaces

Abstract: Large complex formation involved in the thermal decomposition of hydrazine (N 2 H 4) is studied using transition state theory based theoretical kinetics. A comprehensive analysis of the N H and N H 6 potential energy surfaces was performed at the CCSD(T)-F12a/aug-cc-pVTZ//B97x-D3/6-311++G(3df,3pd) level of theory, and pressure-dependent rate coefficients were determined. There are no low-barrier unimolecular decomposition pathways for triazane (n-N 3 H 5), and its formation becomes more significant as the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 64 publications
1
12
1
Order By: Relevance
“…Early works suggested N 2 H 4 decomposes either to a N 2 H 3 + H or NH 2 + NH 2 radical, with subsequent reactions involving the produced radicals producing NH 3 , H 2 , and N 2 . Later, additional kinetics involving interactions with an active N 2 H 2 radical were added. These studies and others were incorporated by Konnov and De Ruyck into a comprehensive mechanism which included NNH, H, and N radical interactions for the first time . More recently, N 3 H 5 and N 4 H 6 intermediates were suggested to participate in N 2 H 4 reaction pathways . Interactions between hydrazine and ammonia mechanisms are reciprocal since N 2 H 4 decomposition produces NH 3 and since NH 3 -derived NH 2 may recombine to produce N 2 H 4 .…”
Section: Nitrogen-based Fuel Oxidation and Decomposition Mechanismsmentioning
confidence: 99%
“…Early works suggested N 2 H 4 decomposes either to a N 2 H 3 + H or NH 2 + NH 2 radical, with subsequent reactions involving the produced radicals producing NH 3 , H 2 , and N 2 . Later, additional kinetics involving interactions with an active N 2 H 2 radical were added. These studies and others were incorporated by Konnov and De Ruyck into a comprehensive mechanism which included NNH, H, and N radical interactions for the first time . More recently, N 3 H 5 and N 4 H 6 intermediates were suggested to participate in N 2 H 4 reaction pathways . Interactions between hydrazine and ammonia mechanisms are reciprocal since N 2 H 4 decomposition produces NH 3 and since NH 3 -derived NH 2 may recombine to produce N 2 H 4 .…”
Section: Nitrogen-based Fuel Oxidation and Decomposition Mechanismsmentioning
confidence: 99%
“…detected it in the gas phase. See Richard and Ball, and Dana et al for computation studies of triazane.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Kim et al 264 and Heo et al 265 also isolated triazane N 3 H 5 in its complexes with Ag + , whereas Forstel et al 266 detected it in the gas phase. See Richard and Ball, 267 and Dana et al 268 for computation studies of triazane.…”
Section: Isotactic Polyazane (Nh)mentioning
confidence: 99%
“…The present model does not consider the large complex formation and doubly protonated species such as H 2 NO 3 + in the thermal decomposition of N 2 H 4 . Green and co-workers investigated and established the mechanism for the reactions in the gas phase using transition state theory-based theoretical kinetics. Lang and Bohn found that the formation of the reactive H 2 NO 3 + can accelerate the decomposition of ammonium dinitramide (NH 4 N­(NO 2 ) 2 ) based on the DFT calculations.…”
Section: Results and Discussionmentioning
confidence: 99%